Lesion heterogeneity and risk of infectious complications following peripheral endobronchial ultrasound. Issue 3 (18th November 2016) - Fortin, Marc; Taghizadeh, Niloofar; Chee, Alex; Hergott, Christopher A.; Dumoulin, Elaine; Tremblay, Alain; MacEachern, Paul
ABSTRACT: Background and objective: The reported incidence of peripheral endobronchial ultrasound (pEBUS)‐related infectious complications is below 1%, although studies have never focused solely on them or reported their risk factors. The goal of this study is to describe our local pEBUS infectious complication rate and characterize patient, lesion and procedural factors associated with infectious complications. Methods: All charts, computed tomography scans and electronic records of patients who underwent a pEBUS at the Foothills Medical Center and South Health Campus Hospital in Calgary between 1 May 2014 and 1 October 2015 were reviewed. Results: One hundred and ninety‐nine pEBUS procedures were included in our study. The local infectious complication rate was 4.0% (8/199). Two lesion characteristics were more frequent in patients who suffered infectious complications: larger lesion diameter ( P = 0.016) and lesion heterogeneity on imaging suggestive of areas of necrosis ( P < 0.001). In a multivariate analysis, only the presence of lesion heterogeneity was significantly associated with infectious complications (OR = 16.74 (2.95–95.08)). The rate of infectious complications in lesions with a heterogeneous appearance was 20.7% (6/29). Conclusion: The rate of infectious complications after pEBUS is elevated when biopsying heterogeneous appearing lesions. This may not have previously been reported as studies of pEBUS focused on smaller and probably rarely necrotic lesions. Future studies of methods to prevent infections complications in pEBUS‐guided biopsies of heterogeneous appearing lesions are warranted. Abstract : Low rates of infectious complications have been reported after peripheral endobronchial ultrasound (pEBUS), but studies have mainly focused on small peripheral pulmonary lesions. This study demonstrates a high rate of infectious complications when performing pEBUS‐guided biopsies of heterogeneous appearing lesions suggestive of necrosis on computed tomography (CT) scan imaging.